Case Report: A concomitant case of eosinophilic granuloma of the spine and Fasciola hepatica infection of the liver in a young patient, and review of the literature - Zhang, Jinri; Li, Haoxian; Wu, Yingcong; Zhang, Dinghao; Xie, Chuhai; Ling, Long; Hu, Hailan; Liu, Qi (Frontiers in Surgery, 2026)
Eosinophilic granuloma (EG) is a benign osteolytic bone lesion and is a localized form of Langerhans cell histiocytosis, most commonly involving the skeletal system. EG is a rare tumor, and involvement of the spine is low. Fascioliasis is a zoonotic disease caused by Fasciola species. The concomitant occurrence of EG and Fasciola hepatica infection is very rare. We report the clinical case of a young man (22 years old) who presented with acute pain in the dorsum. Magnetic resonance imaging revealed a T9 vertebra lesion that was hypointense on T1-weighted images and hyperintense on T2-weighted images. Computerized tomography demonstrated an osteolytic bone lesion in the T9 vertebra. Meanwhile, Doppler ultrasound of the liver displayed multiple echo groups in the bile duct, which suggested Fasciola hepatica infection. The lesion was removed by posterior surgery, during which gray-brown granulation tissue was noted in the T9 vertebra. Histological and immunohistochemical indices confirmed the diagnosis of the EG. Ectopic spinal localization of Fasciola was reported. This case presented a concomitant EG of the T9 vertebra and Fasciola hepatica infection in the liver, which must be distinguished by surgical resection and pathological evaluation.